A New Contextual Look at the Place the Lord has Chosen as his Own in Deuteronomy 12:13–19 - Michael Ufok Udoekpo (E-Journal of Religious and Theological Studies)
Deuteronomy 12, stresses the idea of having a central place of worship, where the Lord has chosen to establish his name. Deuteronomy 12:13-19 is a pericope which forms one of the four parallel laws concerning cult centralization. It stresses the benefits and requirements for cult centralization. It prohibits sacrificial worship at random altars (v. 13), stipulates an exclusive single altar of sacrifice for the Lord (vv.14, 18), sanctions secular slaughter (v. 15), prohibits offerings, donations in towns and blood consumption (vv.16–17), inclusiveness of the Levites and the marginalized of the society and one’s household (v.19). Cognizance of the proliferation worship centers in Nigeria, where the negative effects of African Traditional Religion, still persist, this essay focuses on Deuteronomy 12:13–19, within the larger context of Deuteronomistic History (Josh–2 Kgs). It translates the texts in English and in Efik where necessary. It examines the passage contextually, historically and theologically provides a verse by verse exegesis in order to discover and highlights its pastoral and spiritual benefits or relevance for religious communities in Africa, using a Nigerian faith community of Ikot Ekpene Diocese as a case study.